FUNCTIONAL CAPABILITIES OF A TELEMENTORING SYSTEM USING VIRTUAL REALITY SMART GLASSES IN SURGICAL EDUCATION - Rashidova , R; Vakhidova , A (Uzbekistan Open Conference, 2025)
This article discusses an innovative development of a comprehensive telementoring system that integrates virtual reality smart glasses to provide intraoperative guidance during surgical interventions. The key features of the system include real-time video streaming with augmented visualization of anatomical structures, implementation of tactile prompts, and organization of full-fledged remote mentoring. The work provides a detailed analysis of the system's technical parameters, the algorithmic basis of its functioning, and presents the results of testing within the educational process, demonstrating a significant improvement in both educational and clinical indicators.
Keywords: telementoring; VR smart glasses; intraoperative guidance; surgical navigation; medical education; augmented reality; tactile feedback; postoperative outcomes